A comparative study of jail management of two jail units - Aquino, Adrienne Mae E.; Tungpalan, Mark Anthony C. (2008)
This study evaluates the existing jail services provided by the two jail units such as, health services, food services, water and ventilation services, recreational services, livelihood programs, religious programs, visiting services and privileges of inmates. It also presents the political dynamics among inmates as illustrated by the existence of leaders, gangs and inmates' organization which inevitably help in the efficient management of the jail. This research also demonstrates the perception of jail guards on how jail services are provided in the two jail units. In addition, this study shows the perception of the two jail wardens in the two jail units concerning their active role in the efficient management of their jail of jurisdiction. The information was gathered from inmates and jail personnel including jail guards and jail wardens of the two jail units, Baguio City Jail and Pangasinan Provincial Jail. The data presentation involved discussions on jail services, political dynamics of inmates and perception of jail personnel towards jail management efficiency. Generally, the two jails appear to offer satisfactory services to the inmates, although with some differences in the quality of services. The leaders of the inmates as well as the gangs and organization found in the jails are found out to be helpful in the management of the jails --Author's abstract.